4D printing PLA / TPU composite material based on cold crystallization as well as preparation method and application thereof

By adopting the cold crystallization process in 4D printed PLA/TPU composite materials, the limitations of traditional orthotic materials and complex processes are solved, and the high shape memory performance, mechanical properties and heat resistance of the material are achieved, and the use temperature range is expanded.

CN119505497APending Publication Date: 2025-02-25SICHUAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646353.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The performance of traditional gypsum orthotic materials is limited, making it difficult to dynamically adapt to patient needs, and the process is complex, which limits production scale and efficiency.

Method used

The 4D printed PLA/TPU composite material based on cold crystal is used, and the shape memory, mechanical properties and heat resistance of the material are improved by a twin-screw extruder forming and combined with the cold crystallization process.

Benefits of technology

The shape memory, mechanical properties and heat resistance of the composite material are significantly improved, so that the temporary shape exists stably after cold crystallization, and is not affected by temperature, greatly expanding the use temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505497A_ABST
    Figure CN119505497A_ABST
Patent Text Reader

Abstract

The invention provides a 4D printing PLA / TPU composite material based on cold crystallization as well as a preparation method and application thereof. The composite material is prepared from the following raw materials in percentage by mass: 50 to 100 percent of polylactic acid and 0 to 50 percent of thermoplastic polyurethane. The preparation method comprises the following steps: carrying out vacuum drying treatment on polylactic acid and thermoplastic polyurethane, uniformly mixing according to a ratio, putting into a double-screw extruder, and carrying out melt blending, extrusion and molding to obtain the composite filament. The composite filament meets the material requirements of fused deposition modeling (FDM) 3D printing, and is used for preparing 3D models such as intelligent structures and orthotics. The 3D model shows excellent shape memory performance, high mechanical strength and crystallization capacity. A 3D printing technology is utilized to construct a three-dimensional model, and a cold crystallization process and a 4D printing technology are combined, so that the PLA / TPU composite material can realize transformation from a temporary shape to a second permanent shape under external stimulation, and has an intelligent response function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of shape memory materials, and in particular to a 4D printing PLA / TPU composite material based on cold crystallization, a preparation method and applications thereof. Background Art

[0002] 4D printing technology is a further development based on 3D printing. By introducing the time dimension, the printed object can dynamically change its shape, performance or function under the influence of external stimuli (such as temperature, humidity, light or magnetic field).

[0003] Shape memory polymers (SMPs), as one of the widely used smart materials in 4D printing, have become a research hotspot due to their ability to deform and recover under external stimuli. Common SMPs materials include polylactic acid (PLA) and thermoplastic polyurethane (TPU); polylactic acid (PLA) has good biocompatibility and degradability and is often used in the biomedical field, but its application is limited by its brittleness and low heat resistance. In contrast, thermoplastic polyurethane (TPU) is widely used in fields such as soft tissue engineering due to its excellent elasticity and wear resistance. By compounding PLA with TPU, the material can be given a variety of excellent properties, including biocompatibility, elasticity and high mechanical strength. However, relying solely on the combination of materials is not enough to fully exert its functional effects.

[0004] The shape memory process is divided into two stages: the first stage, the shaping stage, is to heat the permanent shape, shape it into a temporary shape, and then cool it to room temperature to fix the temporary shape. The second stage, the recovery stage, is to heat the temporary shape above the transformation temperature, release the constraints through phase transition, and restore the initial shape.

[0005] Traditional plaster orthoses are difficult to dynamically adapt to the needs of patients due to the limitations of material properties. At the same time, the complexity of its process also makes the production process cumbersome, limiting the scale and efficiency of production. In addition, although plaster orthoses can fix the fracture site, they have poor air permeability, are uncomfortable to wear, and are difficult to adjust the tightness, which can easily cause complications.

[0006] 4D printed orthotics utilize the transition from permanent shape to temporary shape to achieve orthosis shaping with the limbs and meet the needs of adaptive fit. After the temporary shape is shaped and solidified at room temperature, it is stable between room temperature and the transition temperature; but when the temperature rises above the transition temperature again, the temporary shape will immediately return to the initial shape. That is, the stability of the temporary shape is affected by temperature. When the temperature exceeds the transition temperature, the temporary shape will fail and lose its application value. Summary of the invention

[0007] The purpose of the present invention is to provide a 4D printing PLA / TPU composite material based on cold crystallization, which significantly improves the shape memory performance, mechanical properties and heat resistance of the composite material by combining the cold crystallization process.

[0008] Another object of the present invention is to provide a method for preparing a 4D printing PLA / TPU composite material based on cold crystallization. The composite filament prepared by molding with a twin-screw extruder can be used for 3D printing.

[0009] The third object of the present invention is to provide an application of 4D printing PLA / TPU composite materials based on cold crystallization, which provides a new technical path for the design and application of personalized medical devices and intelligent structures under thermal stimulation response.

[0010] The present invention solves the technical problem by adopting the following technical solutions.

[0011] On the one hand, an embodiment of the present invention provides a 4D printing PLA / TPU composite material based on cold crystallization, which includes the following raw materials by mass percentage:

[0012] Polylactic acid 50-100%, thermoplastic polyurethane 0-50%.

[0013] In some embodiments of the present invention, the composite material comprises the following raw materials by mass percentage: 50-90% polylactic acid and 10-50% thermoplastic polyurethane.

[0014] More preferably, the following raw materials are included by mass percentage: 80% polylactic acid and 20% thermoplastic polyurethane.

[0015] PLA (polylactic acid) is a polymer made of lactic acid as the main raw material. It is a new type of biodegradable material. Its raw materials come from renewable plant resources, such as corn starch. As a polymer material with shape memory function, PLA has good compatibility, degradability, mechanical properties and physical properties, and can be used as a substrate for FDM printing.

[0016] TPU (Thermoplastic Polyurethane) is a flexible polymer material with excellent elasticity, wear resistance and low temperature resistance. TPU is a thermoplastic resin and is an ideal FDM printing precursor material.

[0017] On the other hand, an embodiment of the present invention provides a method for preparing a 4D printed PLA / TPU composite material based on cold crystallization, comprising the following steps:

[0018] The polylactic acid and thermoplastic polyurethane are vacuum dried, mixed evenly according to a certain proportion, and then put into a twin-screw extruder for melting, extrusion and molding to obtain composite filaments.

[0019] In some embodiments of the present invention, the extrusion molding parameters of the twin-screw extruder are: the temperatures of the three melting zones from the feed port to the die discharge port are 110°C-140°C, 140°C-170°C, and 170°C-210°C respectively, and the die extrusion temperature is 170°C-210°C; the twin-screw extruder speed is 30-80r / min, and the feed port speed is 20-60r / min.

[0020] In some embodiments of the present invention, the vacuum drying treatment is performed at a temperature of 50-100°C for 8-14 hours.

[0021] In a third aspect, an embodiment of the present invention provides an application of a 4D printing PLA / TPU composite material based on cold crystallization in 4D printing.

[0022] In some embodiments of the present invention, it can be applied to prepare smart structures or orthoses.

[0023] In some embodiments of the present invention, the method for preparing the orthosis comprises the following steps:

[0024] Using the composite material as a raw material, a three-dimensional model is printed out by a 3D printer; the model is placed in a 60-80°C water bath to soften, taken out and attached to the corresponding part of the human body for external force shaping, and cooled to room temperature to fix the temporary shape of the model; under the action of a certain external force, the temporary shape is maintained, and then a cold crystallization treatment is performed, and the orthosis is naturally cooled to room temperature to obtain the orthosis. It should be noted that the temporary shape is not a particularly stable form. When the temperature exceeds its glass transition temperature (Tg), it will deform and return to its initial shape; therefore, when performing a cold crystallization treatment, an external force must be applied to maintain the temporary shape to prevent the model from undergoing a large recovery deformation during the cold crystallization process. On the other hand, the instability of the temporary shape also provides room for operation in the preparation of the orthosis. For example, when preparing the orthoses of Examples 3 and 4, the 3D printed flat three-dimensional model of the orthosis is fitted on the finger or wrist for shaping. After cooling to room temperature, the temporary shape of the finger or wrist orthosis is obtained. Subsequently, the instability of the temporary shape or the elasticity of the model itself is used to remove the orthosis model from the finger or wrist, and then the temporary shape is maintained with external force. After cold crystallization treatment, the permanent shape orthosis model can be obtained.

[0025] In some embodiments of the present invention, the parameters of the 3D printing are: nozzle diameter 0.4-0.6 mm, printing layer thickness 0.2-0.5 mm, nozzle temperature 210-230° C., hot bed temperature 25° C., printing speed 60 mm / s, and filling density 100%.

[0026] In some embodiments of the present invention, the cold crystallization treatment conditions are: cold crystallization treatment is performed at a temperature of 80° C.-120° C. for 10 min-2 h.

[0027] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0028] The composite material provided by the present invention changes a temporary shape into a second permanent shape through a cold crystallization process of the material, so that the temporary shape can be stable and not affected by temperature. Even if it is heated to above the cold crystallization temperature later, the temporary shape can still exist stably, which greatly expands the use temperature range of the temporary shape. This is because after the material is cold crystallized, as long as it is within a range below its melting point, the crystallization can exist stably and is not affected by temperature changes. The temperature rise and fall process of shape memory polymerization within this temperature range may still retain the transition between the glass state and the rubber state, but the shape will not change. After the temporary shape of the first shaping is fixed by the cold crystallization area of ​​the material, a "second permanent shape" is formed. When the temporary shape is transformed into the second permanent shape through cold crystallization, its shape stability increases, so its application in this temperature range will not be affected by temperature.

[0029] In the present invention, PLA / TPU polymer materials are melt-blended and a twin-screw extruder is used to prepare PLA / TPU composite filaments, which meets the material requirements of fused deposition modeling (FDM) 3D printing. A three-dimensional model is constructed using 3D printing technology, and combined with cold crystallization process and 4D printing technology, the PLA / TPU composite material can achieve the transformation from a temporary shape to a permanent shape under external stimulation, and has an intelligent response function. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1SEM images of composite materials with different mass ratios: (a) PLA; (b) PLA / TPU10; (c) PLA / TPU20; (d) PLA / TPU30; (e) PLA / TPU40; (f) PLA / TPU50;

[0032] Figure 2 It is the production process and printing process of PLA / TPU composite filament;

[0033] Figure 3 Schematic diagram of the shape memory programming process for printing a rectangular spline macro;

[0034] Figure 4 Tensile properties and Young's modulus of PLA / TPU composites at different mass ratios (a) tensile stress-strain curve; (b) Young's modulus histogram;

[0035] Figure 5 Dynamic mechanical properties of PLA / TPU composites at different mass ratios; (a) storage modulus curve before cold crystallization treatment; (b) tanδ curve before cold crystallization treatment; (c) storage modulus curve after cold crystallization treatment; (d) tanδ curve after cold crystallization treatment;

[0036] Figure 6 (a) DSC curves of PLA / TPU composites without cold crystallization treatment; (b) DSC curves of cold crystallization treatment;

[0037] Figure 7 Crystallization curves of PLA / TPU composites with different mass ratios after isothermal crystallization for 60 min at (a) 95°C; (b) 100°C; (c) 105°C; (d) 110°C; (e) 115°C and (f) 120°C.

[0038] Figure 8 Melting curves of PLA / TPU composites with different mass ratios after isothermal crystallization for 60 min at (a) 95°C; (b) 100°C; (c) 105°C; (d) 110°C; (e) 115°C and (f) 120°C.

[0039] Fig. 9 The relative crystallinity curves of PLA / TPU composites with different mass ratios after isothermal crystallization for 60 min at (a) 95°C; (b) 100°C; (c) 105°C; (d) 110°C; (e) 115°C and (f) 120°C.

[0040] Fig.10Avrami plots of ln[_ln(1-Xt)] and lnt of PLA / TPU composites with different mass ratios at (a) 95℃; (b) 100℃; (c) 105℃; (d) 110℃; (e) 115℃ and (f) 120℃ after isothermal crystallization for 60min.

[0041] Fig.11 The shape memory recovery process of the printed specimen is triggered by a constant temperature water bath;

[0042] Fig.12 Thermal stimulus response shape memory performance of PLA / TPU composites at different mass ratios (a) Curve of shape recovery rate changing with time; (b) Shape fixation rate and shape recovery rate;

[0043] Fig.13 XRD patterns of PLA / TPU composites at different mass ratios: (a) without cold crystallization treatment; (b) after cold crystallization treatment at 100℃ for 1h.

[0044] Fig.14 Polarized optical micrographs of PLA / TPU20 composites after isothermal crystallization for 0min, 5min, 10min and 60min.

[0045] Fig.15 The process of making flower bud shapes: (a) model design; (b) model slicing; (c) 3D printed image; (d) flower bud shape finalization process;

[0046] Fig.16 Finger orthosis production process (a) model design; (b) model slicing; (c) 3D printed physical image; (d) finger orthosis shaping process; (e) actual wearing effect of finger orthosis;

[0047] Fig.17 The production process of wrist orthosis: (a) model design; (b) model slicing; (c) 3D printed image; (d) right hand wrist orthosis shaping process and actual wearing effect; (e) left hand wrist orthosis shaping process and actual wearing effect. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0049] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0050] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0051] Example 1

[0052] Prepare the composite material and model as follows:

[0053] Step 1: Place the PLA and TPU polymer materials in a vacuum drying oven at 50-100°C for 10 hours;

[0054] Step 2: Mix the polymer material PLA with shape memory function and the flexible polymer material TPU. The PLA and TPU polymer materials are mixed in a mixing ratio of 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50; the corresponding codes are: PLA, PLA / TPU10, PLA / TPU20, PLA / TPU30, PLA / TPU40, and PLA / TPU50 respectively;

[0055] Step 3: Put the mixed raw materials into the twin-screw extruder respectively for extrusion molding, wherein the molding parameters of the twin-screw extruder are: set the temperature of 3 extrusion zones and 1 head zone in sequence from the feed port to the die discharge port area, according to the melting characteristics of PLA and TPU materials, the temperature is 130℃, 160℃, 190℃ and 190℃ respectively; the twin-screw extruder speed is 50r / min, and the feed port speed is 30r / min. In other embodiments of the present invention, the temperature of each area of ​​the twin screw can also be 110℃, 140℃, 170℃ and 170℃, or 140℃, 170℃, 210℃ and 210℃.

[0056] The theoretical diameter of PLA / TPU composite filaments is 1.75 mm, which can meet the requirements of FDM type 3D printers for printing different structural parts.

[0057] Step 4: Design the model to be printed by 3D modeling software, and import it into the slicing software in STL format for slicing; Use the composite filament in step 3 to print the corresponding model through the FDM-3D printer, wherein the printing parameters of the model are set as follows: nozzle diameter 0.4mm, printing layer thickness 0.3mm, nozzle temperature 210℃, hot bed temperature 25℃, printing speed 60mm / s, and filling density 100%. In other embodiments of the present invention, the printing parameters may also be: nozzle diameter 0.6mm, printing layer thickness 0.5mm, nozzle temperature 230℃, hot bed temperature 25℃, printing speed 60mm / s, and filling density 100%; or nozzle diameter 0.5mm, printing layer thickness 0.2mm, nozzle temperature 220℃, hot bed temperature 25℃, printing speed 60mm / s, and filling density 100%.

[0058] Step 5: Place the printed model in a 80°C water bath for shaping, apply a certain external force, cool the temporary shape to room temperature, and fix its temporary shape;

[0059] Step 6: While applying a certain external force to maintain the temporary shape, the molded model is placed at 100°C for cold crystallization for 1 hour;

[0060] Step 7: After cold crystallization, the temporary shape model is cooled to room temperature, and the temporary shape is transformed into a second permanent shape to obtain a 4D printing model.

[0061] The composite materials and 4D printed models made from the above different raw material ratios were subjected to the following tests:

[0062] (1) Microstructure analysis

[0063] The microstructure of each composite filament was analyzed by SEM. Figure 1 As shown, af are PLA, PLA / TPU10, PLA / TPU20, PLA / TPU30, PLA / TPU40 and PLA / TPU50 composite filaments respectively.

[0064] from Figure 1 It can be clearly seen that the smooth and uniform surface of pure PLA, the highly textured surface of PLA / TPU20 blend, and finally the phase separation structure of PLA / TPU50 develop, which indicates that the compatibility of PLA and TPU is limited and highly dependent on the component ratio.

[0065] (2) Mechanical properties test:

[0066] Tensile mechanical experiments were conducted on PLA, PLA / TPU10, PLA / TPU20, PLA / TPU30, PLA / TPU40 and PLA / TPU50 composites;

[0067] Tensile stress-strain curves and Young's modulus data, such as Figure 4 shown; from Figure 4 It can be found that the samples show obvious elasticity and yield behavior before failure. The tensile strength and Young's modulus of PLA / TPU blends gradually decrease with the increase of TPU content. The tensile strength decreases from 76.31MPa of pure PLA to 19.25MPa of PLA / TPU50, and the Young's modulus decreases from 2140.69MPa of pure PLA to 770.58MPa of PLA / TPU50.

[0068] (3) Dynamic mechanical properties:

[0069] The dynamic mechanical properties of PLA, PLA / TPU10, PLA / TPU20, PLA / TPU30, PLA / TPU40 and PLA / TPU50 composites were analyzed and the DMA curves were obtained, such as Figure 5 (a) As shown in the curve, it can be seen that the storage modulus of all composite materials in the range of 50-80°C changes by two orders of magnitude, indicating that the material has a shape memory effect; at about 100°C, the increase in storage modulus is attributed to the cold crystallization phenomenon of PLA; Figure 5 (c) shows that after cold crystallization treatment, the storage modulus of the composite material is significantly increased in the high temperature range.

[0070] (4) Evaluation of melt crystallization behavior:

[0071] The melt crystallization behavior of PLA / TPU composites with different mass ratios was evaluated by DSC method. The second heating scan after eliminating the thermal history and the first heating scan curve after cold crystallization treatment were shown in Figure 2. Figure 6 The main thermal parameters Tg, Tcc, Tm, ΔHm, ΔHcc and Xc are shown in Tables 1 and 2. With the introduction of TPU, the Tg and Tcc of the PLA / TPU composites gradually decreased, with Tg decreasing from 60.06°C of pure PLA to 44.10°C of PLA / TPU50 blends, and Tcc decreasing from 117.32°C to 93.10°C. The results show that TPU promotes the crystallization of PLA segments during heating.

[0072] The crystallinity (Xc) of PLA / TPU composites was calculated by the following formula:

[0073]

[0074] Where: ΔHm is the melting enthalpy of the sample; ΔHcc is the cold crystallization enthalpy of the sample; WPLA is the weight percentage of PLA in the blend; ΔH 0m is the theoretical melting enthalpy of 100% crystalline PLA (93.7 J / g).

[0075] Table 1

[0076] PLA / TPU (wt / wt) <![CDATA[T g (℃)]]> <![CDATA[T cc (℃)]]> <![CDATA[ΔH cc (J / g)]]> <![CDATA[T m (℃)]]> <![CDATA[ΔH m (J / g)]]> <![CDATA[X c (%)]]> 100 / 0 60.06 177.32 41.08 165.23 42.72 1.75 90 / 10 58.04 112.34 36.51 166.03 38.46 2.31 80 / 20 52.52 103.14 28.26 166.93 32.21 5.27 70 / 30 48.67 99.77 25.12 165.26 29.12 6.10 60 / 40 46.76 96.43 19.83 164.46 24.94 9.09 50 / 50 44.10 93.10 17.63 164.46 22.78 10.99

[0077] Table 2

[0078] PLA / TPU (wt / wt) <![CDATA[T g (℃)]]> <![CDATA[T cc (℃)]]> <![CDATA[ΔH cc (J / g)]]> <![CDATA[T m (℃)]]> <![CDATA[ΔH m (J / g)]]> <![CDATA[X c (%)]]> 100 / 0 63.64 - - 169.54 40.08 42.77 90 / 10 60.41 - - 168.67 38.37 45.50 80 / 20 60.30 - - 168.67 37.31 49.77 70 / 30 44.21 - - 166.21 27.28 41.59 60 / 40 45.31 - - 165.41 23.80 42.33 50 / 50 44.64 - - 164.60 21.50 45.89

[0079] The DSC method was used to further evaluate the isothermal crystallization behavior of PLA / TPU composites with different mass ratios at different temperatures (95 °C, 100 °C, 105 °C, 110 °C, 115 °C, and 120 °C), such as Figure 7 The Avrami parameters T1 / 2, G1 / 2, R2, n, k, Tm, △Hf and Xc of the isothermal crystallization of PLA / TPU composites are shown in Table 3; according to the theory of nucleation and crystal growth mechanism, the n value should usually be an integer between 1 and 4. However, in all composites, the actual measured n values ​​are non-integer, which may be attributed to secondary crystallization, complex nucleation mechanism and changes in material density. According to the study of isothermal crystallization kinetics, the crystallization kinetic parameters t1 / 2, G1 / 2 and k values ​​of PLA and PLA / TPU composites all show significant temperature dependence. The crystallinity of PLA and PLA / TPU composites is significantly improved, averaging about 40%.

[0080] The relative crystallinity (Xt) of the sample represents the crystallization process at different times, and its calculation formula is as follows:

[0081]

[0082] dH is the enthalpy value corresponding to the crystallization time dt, t represents the time consumed in the crystallization process, and ∞ represents the time to complete the crystallization;

[0083] The Avrami equation is used to describe the crystallization process, and its logarithmic change formula is as follows:

[0084] ln[ln(1-X t )]=ln k+n ln t

[0085] Where Xt is the relative crystallinity, n is the Avrami index, and k is the crystallization rate parameter;

[0086] Half crystallization time (t 1 / 2 ) is the time required for the relative crystallinity to reach 50%; generally speaking, the shorter the half-crystallization time, the faster the crystallization rate. The half-crystallization time can be calculated by the formula;

[0087]

[0088] Table 3

[0089]

[0090]

[0091]

[0092] (5) Shape memory recovery experiment:

[0093] The shape memory performance of PLA / TPU composites with different mass ratios was tested by thermal stimulus response method. Fig.11 As shown; PLA / TPU composite materials have higher shape fixation rate and recovery rate, such as Fig.12 shown.

[0094] (6) Evaluation of crystallization behavior:

[0095] The crystallization properties of PLA / TPU composites with different mass ratios were evaluated by XRD method, such as Fig.13 As shown; the crystal morphology of PLA / TPU20 matrix material was observed by POM, such as Fig.14 shown.

[0096] In summary, the PLA / TPU20 composite material in the embodiment of the present invention has good shape memory properties and crystallization properties, and has a high load-bearing capacity.

[0097] Example 2

[0098] In this embodiment, a flat flower three-dimensional model component is designed. The component is printed with PLA / TPU20 composite filament. The design of the model component is as follows: Fig.15 As shown in (a), the flat flower model is placed in a constant temperature water bath at 80°C, bent into a temporary flower bud shape, and then cooled at room temperature to be fixed in the temporary flower bud shape; under the action of external force, the temporary flower bud shape is further fixed, and then placed at 100°C for cold crystallization treatment for 1 hour, taken out and cooled to room temperature, and finally the flower bud shape is transformed into a second permanent shape.

[0099] In other embodiments of the present invention, the cold crystallization treatment conditions may also be 80° C., 2 h, or 120° C., 10 min.

[0100] Example 3

[0101] In this embodiment, a three-dimensional model component of a planar finger orthosis is designed. The component is 3D printed using PLA / TPU20 composite filament, and its design is as follows: Fig.16As shown in (a), the planar finger orthosis model is placed in a constant temperature water bath at 80°C to soften, and the softened model is fitted on the finger for shaping, and then cooled at room temperature to fix it as a temporary finger orthosis; since the temporary finger orthosis itself has a certain elastic deformation ability, the finger orthosis can be gently bent to remove it from the finger; then, in order to maintain this temporary shape, the finger orthosis is restrained under the action of external force (for example, lightly tied with a rubber band) to prevent the shape from recovering during the cold crystallization process. Then, the restrained finger orthosis is placed at a temperature of 100°C for cold crystallization for 1 hour. After the treatment is completed, it is taken out and cooled to room temperature. During the cooling process, the finger orthosis can be put on the finger during cooling, or it can be worn on the finger by using the elastic deformation ability of the finger orthosis itself after it is completely cooled to room temperature. Finally, as the temperature drops, the temporary finger orthosis is transformed into a second permanent shape, and the preparation of the finger orthosis is completed.

[0102] Example 4

[0103] In this embodiment, a three-dimensional model component of a flat wrist orthosis is designed. The component is printed with PLA / TPU20 composite filament. The design of the model component is as follows: Fig.17 As shown in (a), the planar wrist orthosis model is placed in a constant temperature water bath at 80°C to soften, and the softened models are respectively attached to the right wrist and the left wrist for shaping, and then cooled at room temperature to be fixed as a temporary wrist orthosis; the temporary wrist orthosis is removed, and the wrist orthosis is fixed under the action of external force, and then placed at 100°C for cold crystallization treatment for 1 hour. After the treatment is completed, it is taken out and cooled to room temperature. During the cooling process, the wrist orthosis can be put on the wrist during cooling, or after it is completely cooled to room temperature, it can be worn on the wrist using the elastic deformation ability of the wrist orthosis itself. Finally, as the temperature drops, the temporary wrist orthosis is transformed into the second permanent shape, and the preparation of the wrist orthosis is completed.

[0104] It should be noted that cold crystallization is a relatively slow process. Using external force to constrain the temporary shape can prevent the model from returning to its initial shape during the cold crystallization process. The recovery process is slow, so only a slight external force is needed to effectively prevent the model from deforming during the cold crystallization process.

[0105] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A 4D printing PLA / TPU composite material based on cold crystallization, characterized in that: The following raw materials are included by mass percentage: Polylactic acid 50-100%, thermoplastic polyurethane 0-50%.

2. The 4D printing PLA / TPU composite material based on cold crystallization according to claim 1, characterized in that: The following raw materials are included by mass percentage: Polylactic acid 80%, thermoplastic polyurethane 20%.

3. A method for preparing a 4D printing PLA / TPU composite material based on cold crystallization as claimed in claim 1 or 2, characterized in that: The following steps are involved: The polylactic acid and thermoplastic polyurethane are vacuum dried, mixed evenly according to a certain proportion, and then put into a twin-screw extruder for melting, extrusion and molding to obtain composite filaments.

4. The method for preparing a 4D printed PLA / TPU composite material based on cold crystallization according to claim 3, characterized in that: The temperature of the vacuum drying treatment is 50-100° C. and the time is 8-14 hours.

5. The method for preparing a 4D printing PLA / TPU composite material based on cold crystallization according to claim 3, characterized in that: The extrusion molding parameters of the twin-screw extruder are as follows: the temperatures of the three melting zones from the feed port to the die discharge port are 110°C-140°C, 140°C-170°C, and 170°C-210°C, respectively, and the die extrusion temperature is 170°C-210°C; the speed of the twin-screw extruder is 30-80r / min, and the speed of the feed port is 20-60r / min.

6. Application of the 4D printing PLA / TPU composite material based on cold crystallization as described in any one of claims 1 to 5 in 4D printing.

7. An application of a 4D printing PLA / TPU composite material based on cold crystallization as claimed in claim 6, characterized in that: Used in preparing smart structures or orthotics.

8. The use of 4D printing PLA / TPU composite materials based on cold crystallization according to claim 7, characterized in that: The method for preparing the orthosis comprises the following steps: The composite material is used as a raw material to print a three-dimensional model through a 3D printer; the model is placed in a 60-80°C water bath to soften, taken out and attached to the corresponding part of the human body for external force shaping, and cooled to room temperature to fix the temporary shape of the model; under the action of external force, cold crystallization treatment is performed, and it is naturally cooled to room temperature to transform the temporary shape into a second permanent shape to obtain the orthosis.

9. The use of 4D printing PLA / TPU composite material based on cold crystallization according to claim 8, characterized in that: The parameters of the 3D printing are: nozzle diameter 0.4-0.6 mm, printing layer thickness 0.2-0.5 mm, nozzle temperature 210-230° C., hot bed temperature 25° C., printing speed 60 mm / s, and filling density 100%.

10. The use of 4D printing PLA / TPU composite material based on cold crystallization according to claim 8, characterized in that: The processing conditions for cold crystallization are: The cold crystallization treatment is carried out at a temperature of 80°C-120°C for 10 min-2 h.